Diagnostics of the functional state of athletes and engaged in fitness based on heart rate variability - A.V. Komarova, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess heart rate variability and determine the type of autonomic regulation in athletes, as well as in people involved in fitness. Methods and structure of the study. We examined 15 athletes, men aged 22-29 years, as well as 15 people involved in fitness, men aged 22-30 years. Both groups of subjects trained five to seven times a week for 2.5 hours, physical activity was of a mixed, predominantly anaerobic-aerobic nature, exercises of a speed-strength, strength orientation were performed. Results and conclusions. The largest group of individuals was found with type III autonomic regulation both in the general sample and separately in each group. This type of regulation is the most favorable for adaptation, it is characterized by a moderate predominance of autonomous regulation of the heart rate, self-regulation is very effective for such individuals. Special attention should always be paid to individuals who belong to type IV; in the studied groups, a small number of individuals with this type of regulation were found. The method of HRV analysis allows you to identify the state of overtraining. No statistically significant differences were found for all indicators of variability, except for the TP indicator (total power of the spectrum) between athletes and people involved in fitness.